PENGARUH E-COMMERCE DAN EKSPEKTASI PENDAPATAN TERHADAP MINAT BERWIRAUSAHA DIKOTA BELOPA - Darlis; Wahida; Hapid (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The existence of different income expectations or it can also be called the expectation of a person's income from business activities, it is increasingly difficult to determine the low and erratic income planning to have a business but if someone has their own business the right to manage it is unlimited, if it is managed properly well, coupled with the responsibility of one's own career is not easy, sometimes the expected results are far from estimates, sometimes beyond our imagination, and vice versa, not in accordance with the original purpose. This study aims to analyze E-Commerce and income expectations on entrepreneurial interest in Belopa City. Sampling research using accidental sampling method with a total of 30 respondents. Data were analyzed using a quantitative approach through Multiple Regression Analysis using the SPSS Application. The results of this study indicate that simultaneously E-Commerce and expectations influence the interest in entrepreneurship in Belopa City. Partially, E-Commerce has a positive and significant effect on entrepreneurial interest in Belopa City. Partially, income expectations have a positive and significant effect on entrepreneurial interest in Belopa City.